Eye evolution: the blurry beginning - Nilsson, Dan-Eric; Arendt, Detlev (Current biology, 2008)
Recent work on the expression of retinal transcription factors and other molecular cues delivers interesting but partly contradictory information on the early phases of eye evolution.